Antagonistic Effects of a Mixture of Low-Dose Nonylphenol and Di-N-Butyl Phthalate (Monobutyl Phthalate) on the Sertoli Cells and Serum Reproductive Hormones in Prepubertal Male Rats In Vitro and In Vivo - Hu, Yang (Public Library of Science, 2014)

(untitled)
The estrogenic chemical nonylphenol (NP) and the antiandrogenic agent di-n-butyl phthalate (DBP) are regarded as widespread environmental endocrine disruptors (EDCs) which at high doses in some species of laboratory animals, such as mice and rats, have adverse effects on male reproduction and development. Given the ubiquitous coexistence of various classes of EDCs in the environment, their combined effects warrant clarification. In this study, we attempted to determine the mixture effects of NP and DBP on the testicular Sertoli cells and reproductive endocrine hormones in serum in male rats based on quantitative data analysis by a mathematical model. In the in vitro experiment, monobutyl phthalate (MBP), the active metabolite of DBP, was used instead of DBP. Sertoli cells were isolated from 9-day-old Sprague-Dawley rats followed by treatment with NP and MBP, singly or combined. Cell viability, apoptosis, necrosis, membrane integrity and inhibin-B concentration were tested. In the in vivo experiment, rats were gavaged on postnatal days 23–35 with a single or combined NP and DBP treatment. Serum reproductive hormone levels were recorded. Next, Bliss Independence model was employed to analyze the quantitative data obtained from the in vitro and in vivo investigation. Antagonism was identified as the mixture effects of NP and DBP (MBP). In this study, we demonstrate the potential of Bliss Independence model for the prediction of interactions between estrogenic and antiandrogenic agents.